Controlling disinfection byproducts from treated wastewater using adsorption with granular activated carbon: Impact of pre-ozonation and pre-chlorination. (1st December 2020) - Verdugo, Edgard M.; Gifford, Mac; Glover, Caitlin; Cuthbertson, Amy A.; Trenholm, Rebecca A.; Kimura, Susana Y.; Liberatore, Hannah K.; Richardson, Susan D.; Stanford, Benjamin D.; Summers, R. Scott; Dickenson, Eric R.V.
Abstract: This study measured chlorine- and chloramine-reactive precursors using formation potential (FP) tests of nine U.S. Environmental Protection Agency (EPA) regulated and 57 unregulated disinfection byproducts (DBPs) in tertiary-filtered wastewater before and after pilot-scale granular activated carbon (GAC) adsorption. Using breakthrough of precursor concentration and of concentration associated calculated cytotoxicity and genotoxicity (by correlating known lethal concentrations reported elsewhere), the performance of three parallel GAC treatment trains were compared against tertiary-filtered wastewater: ozone/GAC, chlorine/GAC, and GAC alone. Results show GAC alone was the primary process, versus ozone or chlorine alone, to remove the largest fraction of total chlorine- and chloramine-reactive DBP precursors and calculated cytotoxicity and genotoxicity potencies. GAC with pre-ozonation removed the most chlorine- and chloramine-reactive DBP precursors followed by GAC with pre-chlorination and lastly GAC without pre-treatment. GAC with pre-ozonation produced an effluent with cytotoxicity and genotoxicity of DBPs from FP that generally matched that of GAC without pre-oxidation; meanwhile removal of toxicity was greater by GAC with pre-chlorination. The cytotoxicity and genotoxicity of DBPs from FP tests did not scale with DBP concentration; for example, more than 90% of the calculated cytotoxicity resulted from 20% of the DBPs, principally from haloacetaldehydes, haloacetamides, and haloacetonitriles. The calculated cytotoxicity and genotoxicity from DBPs associated with FP-chloramination were at times higher than with FP-chlorination though the concentration of DBPs was five times higher with FP-chlorination. The removal of DBP precursors using GAC based treatment was at least as effective as removal of DOC (except for halonitromethanes for GAC without pre-oxidation and with pre-chlorination), indicating DOC can be used as an indicator for DBP precursor adsorption efficacy. However, the DOC was not a good surrogate for total cytotoxicity and genotoxicity breakthrough behavior, therefore, unregulated DBPs could have negative health implications that are disconnected from general water quality parameters, such as DOC, and regulated classes of DBPs. Instead, cytotoxicity and genotoxicity correlate with the concentration of specific classes of unregulated DBPs. Graphical abstract: Image 1 Highlights: Ozonation followed by GAC yielded the lowest DBP formation potential. Chlorination followed by GAC yielded the lowest DBP-associated calculated toxicity. Breakthrough of DOC matched that of DBP concentration but not of toxicity. Breakthrough of DOC was faster than most types of DBP precursors.